The endophallus of Timarcha kiesenwetteri ssp. sagrensis Kuntzen 1911 (Coleoptera: Chrysomelidae: Chrysomelinae) - José Miguel Vela; Mauro Daccordi (Natural History Sciences, 2023)
The endophallus of Timarcha kiesenwetteri ssp. sagrensis is herein described for the first time. Its morphology is simple. It has a long basal lobe and a large medial lobe which narrows progressively to a small apical diverticulum. Timarcha kiesenwetteri is an extremely rare species from Southern Spain. It is so rare it has been found very infrequently in the last century.